Investigation of energy performance and usage behavior of domestic refrigerator freezer using clustering and segmentation - Saidur, Rahman; Masjuki, Haji Hassan; Hasanuzzaman, M.; Kai, G.S. (Journal of Applied Sciences, 2008)
This study carried out the field survey from house to house to garner the information of consumer behavior. In this study the energy consumption 104 refrigerators have been monitored as well. The energy consumption of 104 refrigerators is clustered and segmented to classify the refrigerators of same characteristic in the same group. The capacity of the refrigerator, frequency of door opening and position of refrigerator either near heat source or away from the heat source is considered for clustering and segmentation analysis. The clustering and segmentation in this survey reveal the effect of these factors on the energy performance of the refrigerator.